1972
DOI: 10.1146/annurev.pa.12.040172.002231
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pharmacology: A Review of its Application to Clinical and Basic Science

Abstract: Drugs administered to the maturing host may (a) be used to alleviate diseases peculiar to his age group, (b) undergo alterations in metabolic fate and distribution to influence therapeutic effectiveness as compared with adults, or (c) show unexpected adverse effects as a result of systems placed at risk during development. Pharmacologic treatment of neonatal "physio logic " hyperbilirubinemia has been studied, and drugs undoubtedly will be designed for a specific effect on other diseases characterized by a slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…(43) Estrogens, in contrast, have been shown to decrease hepatic microsomal activity and drug clearance in rodents via a reduction in the amount of microsomal DME protein. (44, 45) The reported effects of progesterones on DME activity are variable and inconsistent with some investigations reporting an inhibitory effect (46) and others reporting an inductive effect. (44)…”
Section: Growth and Sex Hormones As Biochemical Regulators Of Dmesmentioning
confidence: 99%
“…(43) Estrogens, in contrast, have been shown to decrease hepatic microsomal activity and drug clearance in rodents via a reduction in the amount of microsomal DME protein. (44, 45) The reported effects of progesterones on DME activity are variable and inconsistent with some investigations reporting an inhibitory effect (46) and others reporting an inductive effect. (44)…”
Section: Growth and Sex Hormones As Biochemical Regulators Of Dmesmentioning
confidence: 99%
“…Many of the infants were exposed to phenobarbital along with DPH, and the barbiturate (or DPH) could accelerate maturation of oxidative (170,171) as well as conjugative (e.g. 15,16) processes. No dependence of DPH elimination rate on coincident exposure to phe nobarbital was apparent.…”
Section: Drug Oxidation In the Human Neonatementioning
confidence: 99%
“…Pharmacology, Sylvius labs of the University, P.O. Box 9503, 2300 RA LEIDEN, The Netherlands certain drugs and other xenobiotics that are relatively safe when administered to adults (7,8). It has been shown that the deficiency of many drug-metabolizing enzymes in foetuses and neonates is, at least partly, responsible for the increased toxicity in these organisms of compounds which have to be detoxified metabolically.…”
Section: Introductionmentioning
confidence: 99%